TERMINOLOGY FUNDAMENTALS OF LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The science of terminology is relatively young. It originated in the bowels of lexicology as one of its sections 26, 283 p. The development of the theoretical foundations of terminology began in the 1930s. The founder of terminology is considered to be the Austrian scientist O. Wuster, who later headed the Austro-German school of terminology. The main terminology was based on the research results of E. K. Dresena, D. S. Lotte, G.O. Vinokura, A. A. Reformatoskogo. The development and formation of terminology is a process in which several stages are traditionally distinguished